Wpływ technologii sieciowych na reengineering systemów informatycznych zarządzania - Bytniewski, Andrzej (The Impact of Network Technologies on Reengineering of Management Information Systems, 2007)
This article describes how information technologies may influence changes in database construction and organizing and performing the management information systems. The main emphasis is laid on changes in performance of these systems in wire and wireless network.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 287-296